Variabilidade comportamental e aumento da probabilidade de seqüências de respostas com baixa ocorrência inicial em um procedimento de operante livre - Giolo, Juliana Cristina de Carvalho (2010)
The objective of this study was to analyze if the direct reinforcement of variable responding in a free-operant procedure can facilitate learning of a response sequence with low baseline frequency in human repertoires. It also aimed to verify if the distance between lateral keyboards may influence the variable performance. Eighteen participants were divided in three groups of six members each variability, yoked and control. Each group was composed of three participants with nearby keyboards and three participants with distant keyboards. The task involved constructing figures on a computer screen by pressing two keys (right and left) on lateral keyboards. The behavioral unit was a four key press sequence. Sequences that achieved the reinforcement criterion produced parts of the figure and a sound. The participants of the variability and the yoked groups, after a baseline phase in which all target sequences were reinforced, were exposed to a concurrent reinforcement schedule. In this schedule, the least completed sequence during baseline target sequence produced continuous reinforcement (CRF) while the other sequences produced reinforcement if they achieved the established reinforcement criteria. In the variability condition the reinforcement criteria was having the relative frequency of the sequence completed below a threshold value (RDF). In the yoked condition the same reinforcement distribution was used without the demand for variable performance. For the control group, after the baseline, only the target sequences were reinforced in CRF. The results including U indexes, number of completed sequences and percentage of each sequences completed indicates that the RDF contingency was effective to produce variable responding and the most participants that learned to emit target sequences were in the variability group, followed by the yoked group. The distance between the lateral keyboards produced differences in the variability measures for each group